À propos d'un projet en cours d'édition de manuscrits arabes de Tombouctou et d'ailleurs - Bernard Salvaing (Afriques)
After a presentation of research dealing with West African Arabic manuscripts, the author emphasizes that until recently this huge set of documentation has been barely touched, as is particularly visible in the field of scientific editions of sources.Such a deficiency may be due to colonial strategies regarding black islam. But one must emphasize the prejudice existing among many scholars – except a few mostly English-speaking pioneers – about texts that to them seem confusing, texts which cannot be understood without a deep knowledge of Arabic. This apprenticeship is not fostered among the africanists by French scientific institutions, whereas the arabists neglect peripheral islam.However, since 2009, a team of africanists and arabists, led by Georges Bohas, has edited nearly twenty texts, and translated several of them. The author draws up a short descriptive inventory of those documents, while emphasizing the advance in knowledge promised by them.